Surgical treatment of conjunctival tumors - Romanowska, Bożena; Żygulska-Mach, Helena; Bryk, Janusz; Orłowska-Heitzman, Jolanta; Sajak-Hydzik, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 1999)
Estimation of results of treatment of benign and malignant conjunctival tumors. In the years 1994-1997, 153 patients were treated. They were 10-87 years old. Among them there were 84 women and 69 men. Follow-up was 6 moths to 3 years. In 106 cases the lesions affected the conjunctiva only, in 23 cases the conjuntiva and the cornea, in 22 cases the caruncle, and in 2 cases the semilunar fold of conjunctiva. In all cases the lesions were excised after prior diathermal closing of blood vessels. The bottom of each defect was frozen. In 7 patients after excision of extensive conjunctival melanoma, additional irradiation of the area with 106Ru plaque in the dose of 60 Gy to the depth of 2 mm was performed. In 62 cases the influence of treatment on the corneal endothelium and autofluorescence of the lens were estimated. Histopathological examination revealed pigmented naevi in 98 cases, malignant melanoma in 21 cases, and in the remaining cases squamous cell papilloma, hyperplasia of lymphatic system, cysts, basal cell and squamous cell carcinoma, hemangioma, and acanthosis of epithelium. In all patients very good and good functional and aesthetic results were obtained. In 1 case of large conjunctival melanoma recurrence developed, despite of the earlier irradiation. with 106 Ru. Examination of the lens did not reveal a negative influence of the treatment on its autofluorescence. Temporary decrease of the density of endothelium cells was observed in isolated cases.